1968
DOI: 10.1037/h0026211
|View full text |Cite
|
Sign up to set email alerts
|

Delay of gratification, Porteus Maze Test performance, and behavioral adjustment in a delinquent group.

Abstract: This study explored the relationships among a behavioral and verbal measure of delay of gratification, Porteus Maze Test measures of planning ability and foresight (TQ) and impulse control (Q), and ratings of adjustment in a school for delinquent adolescent males. Both measures of delay of gratification were significantly related to the Porteus measures and the adjustment ratings. Delay of gratification was also found to be related, in part, to age and ethnic-group membership, but not IQ. The findings were rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
0

Year Published

1973
1973
2002
2002

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 13 publications
3
14
0
Order By: Relevance
“…The second and third studies report the findings of a preliminary and a follow-up study exploring relationships among some measures of ego function and recidivism in delinquent males. The preliminary study, although dependent upon a small N, replicates and extends the findings of several previous studies (Erikson & Roberts, 1966Roberts & Erikson, 1968) demonstrating that the Porteus (5-score measure of impulsiveness, together with associated constructs, reliably differentiates subgroups of delinquents. The follow-up study, in turn, replicates and extends the findings of the preliminary study.…”
supporting
confidence: 83%
“…The second and third studies report the findings of a preliminary and a follow-up study exploring relationships among some measures of ego function and recidivism in delinquent males. The preliminary study, although dependent upon a small N, replicates and extends the findings of several previous studies (Erikson & Roberts, 1966Roberts & Erikson, 1968) demonstrating that the Porteus (5-score measure of impulsiveness, together with associated constructs, reliably differentiates subgroups of delinquents. The follow-up study, in turn, replicates and extends the findings of the preliminary study.…”
supporting
confidence: 83%
“…Specifically, research into a constellation of constructs associated with impulsivity (e.g., ability to delay gratification, experience of time) define the delinquent as an individual with a short time horizon (Black & Gregson, 1973) who is oriented toward the present (Davids, Kidder, & Reich, 1962), unconcerned about the "social future" (Trommsdorff & Lamm, 1980). and strongly motivated to attain immediate rewards (Roberts, Erikson, Riddle, & Bacon, 1974). Studies of another biopsychological dimension of personality (e.g., sensation seeking; Zuckerman, 1979) have indicated the existence of a positive relationship between antisocial behavior and the desire for involvement in stimulating, pleasurable, and personally gratifying experiences (Romero, 1996;White, Labouvie, & Bates, 1985).…”
Section: Downloaded By [Temple University Libraries] At 11:14 21 Novementioning
confidence: 98%
“…An early study by Mischel (1961) found that self-reported delinquents were less likely than nondelinquents to choose delayed, larger reinforcements over immediate, smaller reinforcements. In a study of reform-school boys, Roberts and Erickson (1968) found significant correlations among delay behavior, supervisor ratings of student adjustment, and performance on a measure of foresight. A recent study by Rapport, Tucker, DuPaul, Merlo, and Stoner (1986) found that hyper-active children were less likely to choose a delayed reward than their normal counterparts.…”
Section: Delay Of Gratification and Psychopathologymentioning
confidence: 99%